Local Competitiveness Fostered through Local Institutions for Entrepreneurship - Martin Andersson; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2014)
We review and assess the role local institutional framework conditions play in fostering local entrepreneurship. The basic premise is that entrepreneurship is a central driver of economic renewal and change, and that institutions affect both the supply and direction of entrepreneurship. While local institutions always develop and operate against the backdrop of national institutional frameworks, in particular in non-federal states, our review shows that there is plenty of room for local initiatives and policies to influence the entrepreneurial climate locally. This pertains to both formal (e.g., taxes, regulations and stringency of enforcement) and informal (e.g., attitudes and social legitimacy) institutions. We further argue that the local institutional environment is essential in any local policy aimed to foster productive (high-impact) entrepreneurship. Favorable local institutions not only increase the odds that a region develops or manage to attract entrepreneurial incumbents, but also the odds that a region reaps the full potential of hosting entrepreneurial and knowledge-intensive activities.
Keywords: D22; H70; L26; M13; O43; R38; 330; Business climate; Entrepreneurship; Institutions; Job creation; Local policies; Startups; Regulations; Entrepreneurship culture